Sedentary Lifestyle and Mental Health: A Phenomenological Study of Non-Sports College Students - Muhamad Nur Bramansyah; Wulandari Putri; Wildan Alfia Nugroho (Journal of Physical Education Health and Sport, 2025)
This study aims to deeply understand the relationship between a sedentary lifestyle and mental health among non-sports students in Indonesia post-pandemic. Using a descriptive qualitative method with a phenomenological approach, 63 students from various non-sports study programs at the Indonesian University of Education were selected through purposive sampling, ultimately selecting 10 students. Data were collected using the ASAQ and DASS-21 questionnaires, semi-structured interviews, observations, and document reviews, then analyzed inductively following the Miles and Huberman model. The results showed that the majority of participants spent more than eight hours per day in passive activities such as sitting, lying down, and using devices, with low awareness of the long-term impacts. Symptoms included stress, anxiety, sleep disturbances, emotional exhaustion, and psychosomatic complaints. Sedentary patterns were formed through academic pressure, limited mobility, minimal social support, and the misperception of rest and laziness. These findings underscore the need for campus-based multidimensional interventions that integrate physical activity promotion and mental health enhancement. This study contributes to the literature by exploring students’ subjective perspectives, providing a basis for relevant health prevention and promotion strategies in the digital age.